Metode Kreatif dalam Bina Iman Anak: Meningkatkan Kreativitas Anak Melalui Permainan Interaktif - Marta Hotnauli Sirumape; Emmeria Tarihoran (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Fostering children’s faith requires creative methods to help children understand the teachings of the Christian faith while also enhancing their creativity. This research aims to explore the effectiveness of creative methods through interactive games in the faith building program at St. John Taum Church. With a case study approach, data was collected through direct observation, interviews with supervisors and children, and documentation of activities. The program involves interactive games that aim to teach Christian teachings in a fun and engaging way. The results of the study show that the interactive game-based creative method not only improves children’s understanding of the teachings of faith but also develops their creative skills, such as critical thinking skills and cooperation in groups. Children became enthusiastic and engaged in activities, while mentors reported an increase in children’s positive attitudes and participation. In conclusion, the creative method through interactive games is effective in increasing children’s creativity in the context of faith building and can be widely applied in religion-based learning activities. The implication of this study is the importance of developing creative methods in religious education and to encourage children’s interest and deeper understanding